Potential biomarkers in early detection of gastric cancer - Kaur, Supreet; Kumar, Ankush; Bhatia, Rohit; Choudhary, Diksha; Kaur, Rajwinder; Chandrasekaran, Balakumar; Abu Dayyih, Wael; Maaita, Majd Nawras; Hourani, Wafa (Frontiers in Pharmacology, 2025)
The annual burden of gastric cancer (GC) is increasing, highlighting a major threat to global public health. An important contributing factor to the increased fatality of the disease is the late stage at which GC is usually detected. Recent advancements in genomic and molecular studies have spearheaded the discovery of novel biomarkers for early-stage GC. Enabled by metabolomic, genetic, epigenetic, and proteomic signatures, these biomarkers have the potential to change the diagnostic outlook for GC. Such biomarkers would allow the detection of disease in its early stages, thereby improving the quality of life of those affected by this disease and also lowering the mortality rate. This review aims to provide a thorough overview of the novel biomarkers in GCs. Furthermore, this review addresses the mechanism by which these biomarkers are linked to the detection of GC and their possible utilization in clinical settings. This review comprises several novel biomarkers such as heat shock protein family A6 (HSPA6), annexin A11 (ANXA11), cell division cycle 42 (CDC42), fibroblast activation protein-alpha (FAP), hepcidin antimicrobial peptide (HAMP), solute carrier family 25 member 4 (SLC25A4), serpin peptidase inhibitor clade H member 1 (SERPINH1), cystatin B, deleted in malignant brain tumors 1 (DMBT1), nuclear paraspeckle assembly transcript 1 (NEAT1), N6-methyladenosine-related lncRNAs, circular RNAs, and proteinase 3 (PRTN3). Thus, the aim of this review is to gather and incorporate the current state of knowledge on this topic to point out the need for persistent research and innovation in the field of identification of GC biomarkers. This will enable the opportunity for new and more effective strategies for combating GC, which will further reduce its global burden and improve patient survival.